INDUSTRIAL ENTERPRISES IN UZBEKISTAN AS THE MAIN LINK OF THE NATIONAL ECONOMY - Xolboyev , Ruzimurod (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
The article analyzes the role of industrial enterprises in the national economy, their types, and modern management approaches. It includes 2024–2025 statistics highlighting growth in production and employment. Keywords: industrial enterprises, national economy, management, modernization, competitiveness, production, employment